2013
DOI: 10.1111/1460-6984.12001
|View full text |Cite
|
Sign up to set email alerts
|

Alternating and sequential motion rates in older adults

Abstract: Normative values for AMR and SMR in both genders and across two older age groups were acquired. Diadochokinetic rates outside such values cannot be attributed to normal ageing, so will merit further clinical investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
85
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(98 citation statements)
references
References 29 publications
11
85
1
1
Order By: Relevance
“…On the one hand, Pierce et al . () found no changes in oral‐DDK rates (neither for AMR nor for SMR tasks) comparing two groups of older adults, aged 65–74 and 75–86 years. The authors suggested that, apart from a decrease in rate from younger to older adulthood (> 65 years), additional slowing might occur mainly after 85 years of age.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…On the one hand, Pierce et al . () found no changes in oral‐DDK rates (neither for AMR nor for SMR tasks) comparing two groups of older adults, aged 65–74 and 75–86 years. The authors suggested that, apart from a decrease in rate from younger to older adulthood (> 65 years), additional slowing might occur mainly after 85 years of age.…”
Section: Introductionmentioning
confidence: 87%
“…) and older adults (Pierce et al . ). However, normative data for other languages are mostly unavailable for clinicians.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…The experiments were performed by repeating one syllable of /pə/, /tə/, and /cə/ for 5 seconds quickly and accurately to measure the number of single syllables. The mean score of the syllable was calculated for 5 seconds, and the mean value was calculated 3-times12 ) .…”
Section: Methodsmentioning
confidence: 99%